Praktik Money Politik dalam Pemilihan Legislatif 2024 Terhadap Demokrasi Lokal Masyarakat Kabupaten Alor - Winda Riandar Koso; Akhmad Syafruddin; Frans B. R. Humau (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to examine the practice of money politics in the 2024 Legislative Elections in Alor Regency and its impact on the quality of democracy in the region. Money politics is a crucial issue in the democratic process because it can undermine election integrity, reduce the quality of public political participation, and create injustice in political representation. This practice has the potential to shift voter orientation, from initially choosing based on the vision, mission, and competence of legislative candidates to being more influenced by material offers. The approach used in this study was qualitative, with data collection techniques through in-depth interviews, direct field observations, and review of relevant documents. In this study, the main participants consisted of voters, legislative candidates, and local political observers. The results of the study indicate that the practice of money politics is still widespread, especially in the run-up to election day. This practice involves giving cash or goods to voters in exchange for votes. The research findings indicate that giving money or goods as compensation leads to a decline in the quality of public political participation. Many voters vote based on the material benefits they receive, rather than the competence or track record of legislative candidates. This has resulted in a decline in public political awareness, with those prioritizing short-term gains over the long-term contributions of legislative candidates to the progress of their regions. Based on the research findings, it can be concluded that money politics in the 2024 Legislative Election in Alor Regency negatively impacts local democracy. This practice undermines public trust in the political process, creates dependency between voters and political elites, and undermines democratic values that should be upheld. Therefore, this study recommends strengthening political education in the community and stricter law enforcement against perpetrators of money politics.